Solid electrolyte material and battery using same

By using solid electrolyte materials composed of Li, Zr and F elements, adjusting the ratio of Li to Zr and the inhomogeneity of the crystal lattice, the problem of insufficient conductivity of lithium ions in the prior art is solved, and the charging and discharging performance and safety of high-performance batteries are improved.

JP7664537B2Active Publication Date: 2025-04-18PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2022500232
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-14
Filing Date
2020-11-12
Publication Date
2025-04-18
Estimated Expiration
2040-11-12

AI Technical Summary

Technical Problem

In the prior art, the lithium ion conductivity of solid electrolyte materials is insufficient, making it difficult to meet the needs of high-performance batteries.

Method used

A solid electrolyte material composed of Li, Zr and F elements has a ratio of Li to Zr less than 3.5, and is measured by X-ray diffraction to meet the ratio of the peak full width and half maximum in a specific angle range of more than 1.06 to ensure the unevenness of the crystal lattice and improve the conductivity of lithium ion.

Benefits of technology

High lithium ion conductivity is achieved, the charging and discharging performance of the battery is improved, and since it does not contain sulfur, the risk of hydrosulfide generated when contacting air is avoided, and safety is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007664537000002
    Figure 0007664537000002
  • Figure 0007664537000003
    Figure 0007664537000003
  • Figure 0007664537000004
    Figure 0007664537000004
Patent Text Reader

Abstract

A solid electrolyte material according to the present disclosure contains Li, Zr, and F. The ratio of the amount of Li with respect to the amount of Zr is less than 3.5. In an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material using Cu-Kα rays, the ratio of the FWHM value of the peak having the highest intensity in the diffraction angle 2θ range of 27.5° to 29.5° inclusive with respect to the FWHM value of the peak corresponding to the (111) plane of Si measured under the same conditions is more than 1.06.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. [Background technology]

[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2011-129312 A Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a solid electrolyte material having high lithium ion conductivity. [Means for solving the problem]

[0005] The solid electrolyte material of the present disclosure is Contains Li, Zr, and F, wherein the ratio of the amount of Li to the amount of Zr is less than 3.5; and In an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material using Cu-Kα radiation, the ratio of the full width at half maximum value of the peak having the highest intensity within a diffraction angle 2θ range of 27.5° or more and 29.5° or less to the full width at half maximum value of the peak corresponding to the Si (111) plane measured under the same conditions is greater than 1.06. Effect of the Invention

[0006] The present disclosure provides a solid electrolyte material having high lithium ion conductivity. [Brief description of the drawings]

[0007] [Figure 1] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment. [Diagram 2] FIG. 2 shows a cross-sectional view of a battery 2000 according to a second embodiment. [Diagram 3] FIG. 3 is a graph showing X-ray diffraction patterns of the solid electrolyte materials according to Examples 1 to 10 and Comparative Example 1. [Figure 4] FIG. 4 is a graph showing a conversion pattern of the solid electrolyte material according to Example 1, obtained by converting the horizontal axis of the graph in FIG. 3 from 2θ to q. [Diagram 5] FIG. 5 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of a solid electrolyte material. [Figure 6] FIG. 6 is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material according to Example 1. [Figure 7] FIG. 7 is a graph showing the initial discharge characteristics of the batteries according to Example 1 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings.

[0009] (First embodiment) The solid electrolyte material according to the first embodiment includes Li, Zr, and F, where the ratio of the amount of substance of Li to the amount of substance of Zr is less than 3.5. In an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material according to the first embodiment using Cu-Kα radiation, the ratio of the full width at half maximum value of the peak having the highest intensity within the range of diffraction angle 2θ of 27.5° or more and 29.5° or less to the full width at half maximum value of the peak corresponding to the (111) plane of Si measured under the same conditions is greater than 1.06. Hereinafter, in an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material, the full width at half maximum value of the peak having the highest intensity within the range of diffraction angle 2θ of 27.5° or more and 29.5° or less is referred to as "FWHM". Furthermore, the full width at half maximum value of the peak corresponding to the (111) plane of Si is referred to as "FWHM Si Here, a Si standard sample is used for Si measured under the same conditions as those for the X-ray diffraction measurement of the solid electrolyte material according to the first embodiment. As the Si standard sample, for example, a standard Si powder manufactured by NIST is used.

[0010] In the solid electrolyte material according to the first embodiment, the above-mentioned "FWHM Si By satisfying the condition that "the ratio of FWHM to FWHM is greater than 1.06," the lattice constant of the resulting crystal phase is non-uniform. As a result, in the solid electrolyte material according to the first embodiment, a wide crystal lattice region is generated, which facilitates lithium ion conduction. Therefore, the solid electrolyte material according to the first embodiment has high lithium ion conductivity. Here, high lithium ion conductivity refers to, for example, a lithium ion conductivity of 2×10 -11 That is, the solid electrolyte material according to the first embodiment has a specific resistance of, for example, 2×10 -11 The ionic conductivity may be 1.0 S / cm or more.

[0011] The solid electrolyte material according to the first embodiment is not a FWHM value, but a FWHM Si Therefore, when identifying the solid electrolyte material according to the first embodiment, it is not necessary to take into account measurement errors caused by a measuring device.

[0012] In the X-ray diffraction pattern of the solid electrolyte material according to the first embodiment, the peak having the highest intensity among the single peaks is present within the range of diffraction angle 2θ of 27.5° or more and 29.5° or less. By using such a peak, the FWHM value can be accurately evaluated. Therefore, the FWHM Si The ratio of the FWHM to the FWHM can be accurately evaluated. Note that a single peak is a peak that does not overlap with another peak.

[0013] The solid electrolyte material according to the first embodiment can be used to obtain a battery having excellent charge / discharge characteristics. An example of the battery is an all-solid-state battery. The all-solid-state battery may be a primary battery or a secondary battery.

[0014] It is desirable that the solid electrolyte material according to the first embodiment does not substantially contain sulfur. The solid electrolyte material according to the first embodiment does not substantially contain sulfur means that the solid electrolyte material does not contain sulfur as a constituent element, except for sulfur that is inevitably mixed in as an impurity. In this case, the amount of sulfur mixed in as an impurity in the solid electrolyte material is, for example, 1 mol % or less. From the viewpoint of safety, it is desirable that the solid electrolyte material according to the first embodiment does not contain sulfur. A solid electrolyte material that does not contain sulfur is excellent in safety because hydrogen sulfide is not generated even when exposed to the atmosphere. The sulfide solid electrolyte disclosed in Patent Document 1 may generate hydrogen sulfide when exposed to the atmosphere.

[0015] The solid electrolyte material according to the first embodiment can have high oxidation resistance because it contains F. This is because F has a high oxidation-reduction potential.

[0016] The solid electrolyte material according to the first embodiment may be substantially composed of Li, Zr, and F. Here, "the solid electrolyte material according to the first embodiment is substantially composed of Li, Zr, and F" means that the molar ratio (i.e., molar fraction) of the total amount of substance of Li, Zr, and F to the total amount of substance of all elements constituting the solid electrolyte material according to the first embodiment is 90% or more. As an example, the molar ratio (i.e., molar fraction) may be 95% or more. The solid electrolyte material according to the first embodiment may be composed only of Li, Zr, and F.

[0017] The solid electrolyte material according to the first embodiment may contain elements that are inevitably mixed in. Examples of such elements are hydrogen, oxygen, or nitrogen. Such elements may be present in the raw material powder of the solid electrolyte material or in the atmosphere for producing or storing the solid electrolyte material.

[0018] In a converted pattern in which the horizontal axis of the X-ray diffraction pattern of the solid electrolyte material according to the first embodiment is converted from the diffraction angle 2θ to q, the ratio of the full width at half maximum value of the peak having the highest intensity within the range of q of 1.94 to 2.08 to the full width at half maximum value of the peak corresponding to the Si (111) plane measured under the same conditions may be greater than 1.06, where q satisfies the formula: q = 4πsinθ / λ, where λ represents the wavelength of the X-ray used in the X-ray diffraction measurement.

[0019] In other words, in the above conversion pattern, a solid electrolyte material in which the ratio of the full width at half maximum value of the peak having the highest intensity within the range of q of 1.94 or more and 2.08 or less to the full width at half maximum value of the peak corresponding to the Si (111) plane measured under the same conditions is greater than 1.06 and contains Li, Zr, and F, is a solid electrolyte material that contains Li, Zr, and F and has a FWHM / FWHM SiIt can be regarded as a solid electrolyte material satisfying >1.06. Therefore, for a solid electrolyte material containing Li, Zr, and F, measurement results obtained using radiation other than X-rays (for example, electron beams) may be converted using the mathematical formula: q = 4πsinθ / λ’ (where λ’ represents the wavelength of the radiation) to obtain a conversion pattern. In the conversion pattern thus obtained, when the condition “the ratio of the value of the full width at half maximum of the peak having the highest intensity within the range of q of 1.94 or more and 2.08 or less to the value of the full width at half maximum of the peak corresponding to the (111) plane of Si measured under the same conditions is greater than 1.06” is satisfied, that solid electrolyte material can be regarded as the solid electrolyte material according to the first embodiment.

[0020] In the solid electrolyte material according to the first embodiment, the ratio of the FWHM Si to the FWHM may be less than 5.0. Thereby, a crystal structure having high ionic conductivity can be maintained. In order to increase the ionic conductivity of the solid electrolyte material, the ratio of the FWHM Si to the FWHM may be 1.25 or more and 2.88 or less.

[0021] The solid electrolyte material according to the first embodiment may contain a crystal phase represented by the following compositional formula (1). Li x ZrF 4+x ···Formula (1) In formula (1), the mathematical formula: 0 < x < 3.5, is satisfied. A solid electrolyte material containing such a crystal phase has high ionic conductivity.

[0022] In order to increase the ionic conductivity of the solid electrolyte material, in formula (1), the mathematical formula: 1.0 ≤ x ≤ 3.0, may be satisfied.

[0023] The upper limit value and the lower limit value of the range of x in formula (1) can be defined by any combination selected from the numerical values of 1.0, 1.5, 1.8, 2.0, 2.2, 2.5, and 3.0.

[0024] The shape of the solid electrolyte material according to the first embodiment is not limited. Examples of the shape are needle-like, spherical, or elliptical. The solid electrolyte material according to the first embodiment may be particles. The solid electrolyte material according to the first embodiment may be formed to have a pellet or plate shape.

[0025] When the shape of the solid electrolyte material according to the first embodiment is, for example, particulate (for example, spherical), the solid electrolyte material may have a median diameter of 0.1 μm or more and 100 μm or less. The median diameter means a particle size at which the cumulative volume in the volume-based particle size distribution is 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzer.

[0026] The solid electrolyte material according to the first embodiment may have a median diameter of 0.5 μm or more and 10 μm or less. This allows the solid electrolyte material to have higher conductivity. Furthermore, when the solid electrolyte material according to the first embodiment is mixed with other materials such as active materials, the solid electrolyte material according to the first embodiment and the other materials are well dispersed.

[0027] <Method of manufacturing solid electrolyte material> The solid electrolyte material according to the first embodiment is produced, for example, by the following method.

[0028] Raw material powders are prepared and mixed to obtain a desired composition. The raw material powders may be, for example, halides.

[0029] For example, when the target composition is Li3ZrF7, the raw material powders LiF and ZrF4 are mixed in a molar ratio of about 3.0:1.0. The raw material powders may be mixed in a pre-adjusted molar ratio to offset composition changes that may occur during the synthesis process.

[0030] The raw material powders are reacted with each other mechanochemically (i.e., using the method of mechanochemical milling) in a mixing device such as a planetary ball mill to obtain a reactant. The reactant may be heat-treated in a vacuum or in an inert atmosphere. Alternatively, a mixture of the raw material powders may be heat-treated in a vacuum or in an inert atmosphere. The heat treatment may be carried out, for example, at 100°C or more and 300°C or less for 1 hour or more. To suppress composition changes during the heat treatment, the raw material powders or the reactant may be heat-treated in a closed container such as a quartz tube.

[0031] Increasing the temperature or time of the heat treatment can decrease the FWHM value of the resulting solid electrolyte material.

[0032] By these methods, the solid electrolyte material according to the first embodiment can be obtained.

[0033] The composition of the solid electrolyte material can be determined, for example, by ICP emission spectroscopy, ion chromatography, inert gas fusion-infrared absorption spectroscopy, or EPMA (Electron Probe Micro Analyzer) method. For example, the composition of Li and Zr can be determined by ICP emission spectroscopy, and the composition of F can be determined by ion chromatography.

[0034] Second embodiment The second embodiment will be described below. The matters described in the first embodiment may be omitted.

[0035] The battery according to the second embodiment includes a positive electrode, a negative electrode, and an electrolyte layer. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material according to the first embodiment. The battery according to the second embodiment has excellent charge / discharge characteristics because it contains the solid electrolyte material according to the first embodiment. The battery may be an all-solid-state battery.

[0036] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment.

[0037] The battery 1000 according to the second embodiment includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203.

[0038] The positive electrode 201 contains positive electrode active material particles 204 and solid electrolyte particles 100 .

[0039] The electrolyte layer 202 contains an electrolyte material, for example, a solid electrolyte material.

[0040] The negative electrode 203 contains negative electrode active material particles 205 and solid electrolyte particles 100 .

[0041] The solid electrolyte particle 100 is a particle containing the solid electrolyte material according to the first embodiment. The solid electrolyte particle 100 may be a particle made of the solid electrolyte material according to the first embodiment, or a particle containing the solid electrolyte material according to the first embodiment as a main component. Here, the particle containing the solid electrolyte material according to the first embodiment as a main component means a particle in which the component contained most abundantly in terms of molar ratio is the solid electrolyte material according to the first embodiment.

[0042] The positive electrode 201 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The material is, for example, a positive electrode active material (for example, positive electrode active material particles 204).

[0043] Examples of the positive electrode active material are lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are Li(Ni,Co,Al)O2, Li(Ni,Co,Mn)O2, or LiCoO2. In this disclosure, the notation "(Ni,Co,Al)" in the chemical formula indicates at least one element selected from the group of elements in parentheses. That is, "(Ni,Co,Al)" is synonymous with "at least one selected from the group consisting of Ni, Co, and Al." The same applies to other elements.

[0044] The positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median diameter of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 are well dispersed in the positive electrode 201. This improves the charge / discharge characteristics of the battery. When the positive electrode active material particles 204 have a median diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 is improved. This allows the battery to operate at high power.

[0045] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This allows the positive electrode active material particles 204 and the solid electrolyte particles 100 to be well dispersed in the positive electrode 201.

[0046] From the viewpoint of the energy density and output of the battery, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0047] A coating layer may be formed on at least a part of the surface of the positive electrode active material particle 204. The coating layer may be formed on the surface of the positive electrode active material particle 204, for example, before mixing with the conductive assistant and the binder. Examples of the coating material contained in the coating layer are a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte. When the solid electrolyte particle 100 contains a sulfide solid electrolyte, the coating material may contain the solid electrolyte material according to the first embodiment in order to suppress oxidative decomposition of the sulfide solid electrolyte. When the solid electrolyte particle 100 contains the solid electrolyte material according to the first embodiment, the coating material may contain an oxide solid electrolyte in order to suppress oxidative decomposition of the solid electrolyte material. Lithium niobate, which has excellent stability at high potential, may be used as the oxide solid electrolyte. By suppressing oxidative decomposition, it is possible to suppress an overvoltage rise of the battery.

[0048] From the viewpoint of the energy density and output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.

[0049] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may be a solid electrolyte layer.

[0050] The electrolyte layer 202 may contain the solid electrolyte material according to the first embodiment. The electrolyte layer 202 may be composed only of the solid electrolyte material according to the first embodiment. The electrolyte layer 202 may be composed only of a solid electrolyte material different from the solid electrolyte material according to the first embodiment. Examples of the solid electrolyte material different from the solid electrolyte material according to the first embodiment are Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, Li3(Al,Ga,In)X6, or LiI. Here, X is at least one selected from the group consisting of F, Cl, Br, and I.

[0051] Hereinafter, the solid electrolyte material according to the first embodiment will be referred to as a first solid electrolyte material, and a solid electrolyte material different from the solid electrolyte material according to the first embodiment will be referred to as a second solid electrolyte material.

[0052] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed in the electrolyte layer 202. A layer made of the first solid electrolyte material and a layer made of the second solid electrolyte material may be stacked along the stacking direction of the battery 1000.

[0053] FIG. 2 shows a cross-sectional view of a battery 2000 according to a second embodiment.

[0054] 2, the battery 2000 may include a positive electrode 201, a first electrolyte layer 212, a second electrolyte layer 222, and a negative electrode 203. That is, the electrolyte layer 202 may include the first electrolyte layer 212 and the second electrolyte layer 222. The first electrolyte layer 212 is disposed between the positive electrode 201 and the negative electrode 203. The second electrolyte layer 222 is disposed between the first electrolyte layer 212 and the negative electrode 203.

[0055] In the battery 2000, the first electrolyte layer 212 may contain the solid electrolyte material according to the first embodiment. Since the solid electrolyte material according to the first embodiment has high oxidation resistance, the solid electrolyte material contained in the second electrolyte layer 222 can be used without being oxidized. As a result, the charge / discharge efficiency of the battery can be improved.

[0056] In the battery 2000, the solid electrolyte material contained in the second electrolyte layer 222 may have a lower reduction potential than the solid electrolyte material contained in the first electrolyte layer 212. This allows the solid electrolyte material contained in the first electrolyte layer 212 to be used without being reduced. As a result, the charge / discharge efficiency of the battery can be improved. For example, when the first electrolyte layer 212 contains the solid electrolyte material according to the first embodiment, the second electrolyte layer 222 may contain a sulfide solid electrolyte to suppress reductive decomposition of the solid electrolyte material.

[0057] From the viewpoint of the energy density and output of the battery, the electrolyte layer 202 may have a thickness of 1 μm or more and 1000 μm or less.

[0058] The negative electrode 203 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The material is, for example, a negative electrode active material (for example, negative electrode active material particles 205).

[0059] Examples of the negative electrode active material are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicides. The metal material may be a single metal or an alloy. Examples of the metal material are lithium metal or lithium alloys. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (i.e., Si), tin (i.e., Sn), silicides, or tin compounds.

[0060] The negative electrode active material may be selected in consideration of the reduction resistance of the solid electrolyte material contained in the negative electrode 203. For example, when the negative electrode 203 contains the solid electrolyte material according to the first embodiment, the negative electrode active material may be a material capable of absorbing and releasing lithium ions at 0.27 V or more versus lithium. Examples of such negative electrode active materials are titanium oxide, indium metal, or lithium alloys. An example of titanium oxide is Li4Ti5O 12 , LiTi2O4, or TiO2. By using the above-mentioned negative electrode active material, it is possible to suppress the reductive decomposition of the solid electrolyte material according to the first embodiment contained in the negative electrode 203. As a result, it is possible to improve the charge / discharge efficiency of the battery.

[0061] The negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median diameter of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 are well dispersed in the negative electrode 203. This improves the charge / discharge characteristics of the battery. When the negative electrode active material particles 205 have a median diameter of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 is improved. This allows the battery to operate at high power.

[0062] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This allows the negative electrode active material particles 205 and the solid electrolyte particles 100 to be well dispersed in the negative electrode 203.

[0063] In the negative electrode 203 from the viewpoint of battery energy density and output, the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.

[0064] From the viewpoint of the energy density and output of the battery, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.

[0065] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material for the purpose of increasing ion conductivity, chemical stability, and electrochemical stability. Examples of the second solid electrolyte material include a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, or an organic polymer solid electrolyte.

[0066] In the present disclosure, a "sulfide solid electrolyte" refers to a solid electrolyte containing sulfur. An "oxide solid electrolyte" refers to a solid electrolyte containing oxygen. The oxide solid electrolyte may contain anions other than oxygen (excluding sulfur anions and halogen anions). A "halide solid electrolyte" refers to a solid electrolyte containing a halogen element and not containing sulfur. The halide solid electrolyte may contain not only a halogen element but also oxygen.

[0067] The second solid electrolyte material may be a sulfide solid electrolyte.

[0068] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 It is.

[0069] When the electrolyte layer 202 contains the solid electrolyte material according to the first embodiment, the negative electrode 203 may contain a sulfide solid electrolyte in order to suppress reductive decomposition of the solid electrolyte material. By covering the negative electrode active material with the electrochemically stable sulfide solid electrolyte, it is possible to suppress the solid electrolyte material according to the first embodiment from coming into contact with the negative electrode active material. As a result, the internal resistance of the battery can be reduced.

[0070] The second solid electrolyte material may be an oxide solid electrolyte.

[0071] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or elemental substitutions thereof; (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGeO 16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4 or elemental substitutes thereof; (iv) Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an elemental substitution product thereof; or (v) Li3PO4 or its N-substituted derivatives, It is.

[0072] As mentioned above, the second solid electrolyte material may be a halide solid electrolyte.

[0073] Examples of halide solid electrolytes are Li2MgX4, Li2FeX4, Li(Al,Ga,In)X4, Li3(Al,Ga,In)X6, or LiI, where X is at least one selected from the group consisting of F, Cl, Br, and I.

[0074] Other examples of halide solid electrolyte materials are Li a Me b Y c X6. Here, a+mb+3c=6 and c>0 are satisfied. Me is at least one selected from the group consisting of metal elements and metalloid elements other than Li and Y. m represents the valence of Me. "Metalloid elements" are B, Si, Ge, As, Sb, and Te. "Metal elements" are all elements included in Groups 1 to 12 of the periodic table (excluding hydrogen) and all elements included in Groups 13 to 16 of the periodic table (excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S, and Se).

[0075] To enhance the ionic conductivity of the halide solid electrolyte material, Me may be at least one selected from the group consisting of Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta, and Nb. The halide solid electrolyte may be Li3YCl6 or Li3YBr6.

[0076] The second solid electrolyte material may be an organic polymer solid electrolyte.

[0077] An example of the organic polymer solid electrolyte is a compound of a polymer compound and a lithium salt.

[0078] The polymer compound may have an ethylene oxide structure. A polymer compound having an ethylene oxide structure can contain a large amount of lithium salt, and therefore can further increase ionic conductivity.

[0079] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.

[0080] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.

[0081] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.

[0082] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate. One type of non-aqueous solvent selected from these may be used alone, or a combination of two or more types of non-aqueous solvents selected from these may be used.

[0083] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / L or more and 2 mol / L or less.

[0084] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.

[0085] Examples of cations contained in ionic liquids are: (i) Aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium salts, (ii) aliphatic cyclic ammonium such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums, or (iii) nitrogen-containing heterocyclic aromatic cations such as pyridiniums or imidazoliums; It is.

[0086] An example of an anion contained in an ionic liquid is PF6 - , BF4 - , SbF6 - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - It is.

[0087] The ionic liquid may contain a lithium salt.

[0088] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles.

[0089] Examples of binders are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, or carboxymethylcellulose. Copolymers may also be used as binders. Examples of such binders are copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. A mixture of two or more materials selected from these may be used as a binder.

[0090] At least one of the positive electrode 201 and the negative electrode 203 may contain a conductive additive to reduce electronic resistance.

[0091] Examples of the conductive additive include: (i) Graphites, such as natural or synthetic graphite; (ii) Carbon blacks such as acetylene black or ketjen black; (iii) conductive fibers, such as carbon or metal fibers; (iv) fluorocarbons, (v) Metal powders such as aluminum; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) a conductive metal oxide, such as titanium dioxide; or (viii) conductive polymers such as polyaniline, polypyrrole, or polythiophene; In order to reduce costs, the above-mentioned conductive assistant (i) or (ii) may be used.

[0092] Examples of the shape of the battery according to the second embodiment are a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.

[0093] The battery according to the second embodiment may be manufactured, for example, by preparing a material for forming a positive electrode, a material for forming an electrolyte layer, and a material for forming a negative electrode, and producing a laminate in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order by a known method. EXAMPLES

[0094] Hereinafter, the present disclosure will be described in more detail with reference to examples and comparative examples.

[0095] <Example 1> (Preparation of solid electrolyte materials) In an argon atmosphere having a dew point of -60°C or less (hereinafter referred to as "dry argon atmosphere"), LiF and ZrF4 were prepared as raw material powders in a molar ratio of LiF:ZrF4 = 3.0:1.0. These raw material powders were pulverized and mixed in a mortar. The obtained mixed powder was milled at 500 rpm for 12 hours using a planetary ball mill. In this manner, a powder of the solid electrolyte material according to Example 1 was obtained. The solid electrolyte material according to Example 1 had a composition represented by Li3ZrF7.

[0096] (Evaluation of full width at half maximum) FIG. 3 is a graph showing the X-ray diffraction pattern of the solid electrolyte material according to Example 1.

[0097] The X-ray diffraction pattern of the solid electrolyte material according to Example 1 was measured using an X-ray diffractometer (MiniFlex600, Rigaku) ​​in a dry environment with a dew point of -50°C or less. Measurement was performed by the θ-2θ method using Cu-Kα radiation (wavelengths 1.5405 Å and 1.5444 Å) as the X-ray source. The measurement angle interval was 0.01°. The divergence angle of the divergence slit was 0.25°. The slit width of the longitudinal limiting slit was 5 mm.

[0098] The value of the diffraction angle 2θ of the peak having the highest intensity within the range of the diffraction angle 2θ of 27.5° or more and 29.5° or less is taken as 2θ top The intensity of the peak is I top The intensity at a diffraction angle 2θ of 29.5° was defined as I bg That is, I bg represents the baseline intensity. I top Half value of I htop is [(I top -I bg ) / 2+I bg ].

[0099] 27.5° or more and 2θ top Within the range of the diffraction angle 2θ below, I htop The diffraction angle 2θ that gives the closest intensity to 2θ L 2θ top Within the range of I and 29.5° htop The diffraction angle 2θ that gives the closest intensity to 2θ H The FWHM is 2θ H and 2θ L The FWHM of the solid electrolyte material according to Example 1 was 0.42 deg.

[0100] Next, X-ray diffraction measurement was performed on the Si crystal powder under the same conditions as for the solid electrolyte material of Example 1. The value of the diffraction angle 2θ of the peak having the highest intensity within the range of the diffraction angle 2θ of 28.0° or more and 28.6° or less was determined as 2θ top The intensity of the peak is I top The intensity at a diffraction angle 2θ of 28.0° was defined as I bgAs a result, the FWHM of the Si crystal powder Si The angle was 0.16 deg. The silicon crystal powder used was the silicon standard sample "SRM 640d (NIST)."

[0101] (Changing the horizontal axis of the X-ray diffraction pattern) The horizontal axis of the X-ray diffraction pattern of the solid electrolyte material according to Example 1 shown in FIG. 3 was converted from the diffraction angle 2θ to q. Here, the formula: q=4πsinθ / λ is satisfied. λ is the wavelength of the X-ray used in the X-ray diffraction measurement. In this way, the conversion pattern of the solid electrolyte material according to Example 1 was obtained. FIG. 4 is a graph showing the conversion pattern of the solid electrolyte material according to Example 1 obtained by converting the horizontal axis of the graph in FIG. 3 from 2θ to q.

[0102] (Evaluation of ionic conductivity) FIG. 5 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of the solid electrolyte material.

[0103] The pressure molding die 300 had an upper punch 301, a frame 302, and a lower punch 303. The frame 302 was made of insulating polycarbonate. The upper punch 301 and the lower punch 303 were made of electronically conductive stainless steel.

[0104] Using the pressure molding die 300 shown in FIG. 5, the ionic conductivity of the solid electrolyte material according to Example 1 was evaluated by the following method.

[0105] In a dry atmosphere having a dew point of −30° C. or less, the powder of the solid electrolyte material according to Example 1 was filled into the inside of the pressure molding die 300. In the inside of the pressure molding die 300, a pressure of 400 MPa was applied to the solid electrolyte material according to Example 1 using the upper punch 301 and the lower punch 303.

[0106] While the pressure was still applied, the upper punch 301 and the lower punch 303 were connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The upper punch 301 was connected to a working electrode and a terminal for measuring potential. The lower punch 303 was connected to a counter electrode and a reference electrode. The impedance of the solid electrolyte material was measured by electrochemical impedance measurement at room temperature.

[0107] FIG. 6 is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material according to Example 1.

[0108] In FIG. 6, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest was considered to be the resistance value for the ion conduction of the solid electrolyte material. The real value is indicated by the arrow R SE Using the resistance value, the ionic conductivity was calculated based on the following formula (2). σ = (R SE ×S / t) -1 (2) Here, σ represents ion conductivity. S represents the contact area of ​​the solid electrolyte material with the punch upper portion 301 (equal to the cross-sectional area of ​​the hollow portion of the frame mold 302 in FIG. 5). R SE represents the resistance value of the solid electrolyte material in impedance measurement, and t represents the thickness of the solid electrolyte material (i.e., the thickness of the layer formed from the powder 101 of the solid electrolyte material in FIG. 5).

[0109] The ionic conductivity of the solid electrolyte material according to Example 1 measured at 25° C. was 6.19×10 -8 S / cm.

[0110] (Battery Construction) In a dry argon atmosphere, the solid electrolyte material according to Example 1 and the active material LiCoO2 were prepared in a volume ratio of 30:70. These materials were mixed in an agate mortar. In this way, a positive electrode mixture was obtained.

[0111] Next, LiCl and YCl3 were prepared in a molar ratio of LiCl:YCl3 = 3:1. These materials were ground and mixed in a mortar. The resulting mixture was milled at 500 rpm for 12 hours using a planetary ball mill. In this way, a halide solid electrolyte (hereinafter referred to as "LYC") having a composition represented by Li3YCl6 was obtained.

[0112] In an insulating cylinder having an inner diameter of 9.5 mm, LYC (70 mg), the solid electrolyte material according to Example 1 (33 mg), and the above-mentioned positive electrode mixture (9.1 mg) were laminated in this order. A pressure of 300 MPa was applied to the obtained laminate, and a second electrolyte layer formed from LYC, a first electrolyte layer formed from the solid electrolyte material according to Example 1, and a positive electrode were formed. That is, the first electrolyte layer formed from the solid electrolyte material according to Example 1 was sandwiched between the second electrolyte layer and the positive electrode. The thicknesses of the second electrolyte layer and the first electrolyte layer were 450 μm and 150 μm, respectively.

[0113] Next, metal In (thickness: 200 μm) was laminated on the second electrolyte layer. A pressure of 80 MPa was applied to the resulting laminate to form a negative electrode.

[0114] Next, current collectors made of stainless steel were attached to the positive and negative electrodes, and current collecting leads were attached to the current collectors.

[0115] Finally, the inside of the insulating cylinder was isolated from the outside atmosphere by using an insulating ferrule, and the inside of the cylinder was sealed. In this manner, the battery according to Example 1 was obtained.

[0116] (Charge / discharge test) 7 is a graph showing the initial discharge characteristics of the battery according to Example 1. The initial discharge characteristics were measured by the following method.

[0117] The battery according to Example 1 was placed in a thermostatic chamber at 85°C.

[0118] 27μA / cm 2 The battery according to Example 1 was charged until a voltage of 3.6 V was reached at a current density of 0.02 C, which corresponds to a 0.02 C rate.

[0119] Next, 27 μA / cm 2 The battery according to Example 1 was discharged at a current density of 0.1 V until a voltage of 1.9 V was reached.

[0120] As a result of the charge / discharge test, the battery according to Example 1 had an initial discharge capacity of 639 μAh.

[0121] <Examples 2 to 10> (Preparation of solid electrolyte materials) In Examples 2 to 7, LiF and ZrF4 were prepared as raw material powders in a molar ratio of LiF:ZrF4=x:1. Except for the above, the solid electrolyte materials according to Examples 2 to 7 were obtained in the same manner as in Example 1. The value of x is shown in Table 1.

[0122] In Examples 8 to 10, LiF and ZrF4 were prepared as raw material powders in a molar ratio of LiF:ZrF4=x:1. The mixed raw material powders were milled and then heat-treated for 1 hour. Except for the above, the solid electrolyte materials according to Examples 8 to 10 were obtained in the same manner as in Example 1.

[0123] The value of x in each of Examples 2 to 10 and the heat treatment temperature in each of Examples 8 to 10 are shown in Table 1. In Table 1, "BM" represents milling treatment using a planetary ball mill.

[0124] (Evaluation of full width at half maximum) The FWHM of the solid electrolyte materials according to Examples 2 to 10 was calculated in the same manner as in Example 1. FWHM and FWHM / FWHM Si The values ​​are shown in Table 1.

[0125] (Evaluation of ionic conductivity) The ionic conductivity of the solid electrolyte materials according to Examples 2 to 10 was measured in the same manner as in Example 1. The measurement results are shown in Table 1.

[0126] (Battery Construction) The solid electrolyte materials according to Examples 2 to 10 were used to obtain the batteries according to Examples 2 to 10 in the same manner as in Example 1.

[0127] (Charge / discharge test) The batteries according to Examples 2 to 10 were subjected to a charge / discharge test in the same manner as in Example 1. The batteries according to Examples 2 to 10 were successfully charged and discharged in the same manner as in Example 1.

[0128] <Comparative Example 1> In a dry argon atmosphere, LiF and ZrF4 were prepared as raw material powders in a ratio of LiF:ZrF4=2:1. The raw material powders were mixed in a mortar and then formed into pellets. The obtained pellet-shaped mixed powder was heat-treated at 450°C for 5 hours. In this manner, a powder of the solid electrolyte material according to Comparative Example 1 was obtained.

[0129] The FWHM of the solid electrolyte material according to Comparative Example 1 was calculated in the same manner as in Example 1. The results are shown in Table 1.

[0130] The ionic conductivity of the solid electrolyte material according to Comparative Example 1 was measured in the same manner as in Example 1. The results are shown in Table 1.

[0131] A battery according to Comparative Example 1 was obtained in the same manner as in Example 1, using the solid electrolyte material according to Comparative Example 1. A charge / discharge test was carried out on the battery according to Comparative Example 1 in the same manner as in Example 1. As a result, the battery according to Comparative Example 1 had an initial discharge capacity of 0.01 μAh or less. That is, the battery according to Comparative Example 1 was neither charged nor discharged.

[0132] [Table 1]

[0133] <Consideration> The solid electrolyte materials of Examples 1 to 10 have a melting point of 2×10 -11 It has high ionic conductivity of over S / cm.

[0134] The batteries according to Examples 1 to 10 were all charged and discharged at 85° C. On the other hand, the battery according to Comparative Example 1 was neither charged nor discharged.

[0135] The solid electrolyte materials according to Examples 1 to 10 do not contain sulfur and therefore do not generate hydrogen sulfide.

[0136] As described above, the solid electrolyte material according to the present disclosure is suitable for providing a battery that has high lithium ion conductivity and can be charged and discharged well. [Industrial Applicability]

[0137] The solid electrolyte material of the present disclosure is used, for example, in an all-solid-state lithium ion secondary battery.

Claims

1. A solid electrolyte material, Contains Li, Zr, and F; Here, the ratio of the amount of substance of Li to the amount of substance of Zr is less than 3.5; In an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material using Cu-Kα radiation, the ratio of the full width at half maximum value of a peak having the highest intensity within a diffraction angle 2θ range of 27.5° or more and 29.5° or less to the full width at half maximum value of a peak corresponding to the Si (111) plane measured under the same conditions is greater than 1.06; and Contains a crystalline phase represented by the following composition formula (1): Li x ZrF 4+x...Formula (1) where the formula: 0<x<3.5 is satisfied. Solid electrolyte material.

2. In a converted pattern obtained by converting the horizontal axis of the X-ray diffraction pattern from the diffraction angle 2θ to q, the ratio of the full width at half maximum value of the peak having the highest intensity within the range of q of 1.94 or more and 2.08 or less to the full width at half maximum value of the peak corresponding to the Si (111) plane measured under the same conditions is greater than 1.06, Here, q=4πsinθ / λ, λ represents the wavelength of the X-rays used in the X-ray diffraction measurement; The solid electrolyte material according to claim 1 .

3. The formula: 1.0≦x≦3.0 is satisfied; The solid electrolyte material according to claim 1 or 2.

4. positive electrode, a negative electrode, and an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 3. battery.

5. the electrolyte layer includes a first electrolyte layer and a second electrolyte layer; the first electrolyte layer is disposed between the positive electrode and the negative electrode; the second electrolyte layer is disposed between the first electrolyte layer and the negative electrode; The first electrolyte layer contains the solid electrolyte material.

5. The battery of claim 4.

Citation Information

Patent Citations

  • Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery

    JP2011129312A

  • Solid electrolyte, solid electrolyte layer, and solid electrolyte battery

    WO2021024783A1